Rapid and reversible adaptation of a clinical linear accelerator for electron FLASH radiotherapy - Schneider, Frank; Bauer, Cornelius Jonathan; Göbel, Ida Dorothea; King, Clarence; Spadea, Maria Francesca; Seco, Joao; Giordano, Frank Anton; Fleckenstein, Jens (Physica medica, 2025)
Purpose - The aim of this work was to establish a procedure that allows the conversion of a standard clinical LINAC into a “FLASH” LINAC capable of delivering ultra-high dose rates above 40 Gy/s, with minimal, fully reversible modifications to the device. A dosimetric characterization of the resulting treatment beam is presented. - Methods - A LINAC was modified to emit a 10 MeV electron FLASH beam. Modifications included the integration of a pulse control unit which consisted out of a scintillation detector and a transistor circuit. Beam parameters were optimized to maximize dose output. Beam characterization measurements were performed with different detectors in water: ionization chamber, diamond detector, radiographic films and scintillation detector. The resulting doses per pulse (DPP) and dose rates at different source-surface-distances (SSD) as well as the output reproducibility were determined. The beam was characterized with depth dose curves and lateral profiles. - Results - Conversion of a LINAC to FLASH mode was feasible in less than 30 min. Output was between DPPSSD=56cm = 1.69 ± 0.02 Gy and DPPSSD=100cm = 0.53 ± 0.01 Gy or dose rates between 676 ± 8 Gy/s and 213 ± 4 Gy/s. Reproducibility of DPP was better than 0.8 %. FLASH depth dose curves showed a higher range (R80 = 39.8 mm vs. 34.6 mm) and lateral beam profiles had a reduced flatness (from 5.5 % to 12.7 %) at SSD = 56 cm. - Conclusion - We present a fully reversible conversion method requiring minimal modifications to a LINAC to produce electron FLASH beams. The achieved DPP and mean dose rates demonstrated high reproducibility, meeting criteria for FLASH applications, and markedly simplifying access to this technology for broader implementation.